Analisis risiko kecelakaan kerja dengan Metode HIRARC dan Diagram Fishbone di Divisi Pergudangan pada PT Z - Wulandari, Aisyah Eka; Iriani, Iriani (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The warehouse is the "spearhead" that supports all company activities. In PT Z's warehouse, the process of receiving, retrieving, and moving goods still has the potential for work accidents. Hazard identification was carried out using the HIRARC and Fishbone Diagram methods to determine the risks and causes. The results of the study showed that there were six activities with seven potential hazards, of which four hazards were classified as medium risk and three others were low risk. Recommendations for improvement include strengthening SOPs for the use of PPE, maintaining the cleanliness and safety of the work area, adding K3 signs, using material handling tools, and improving air ventilation. No potential high-risk hazards were found, reflecting the success of risk management in the warehouse. However, regular evaluations, employee training, and strengthening mitigation are still needed to minimize the risk of future work accidents.